PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MENGGUNAKAN MACROMEDIA FLASH MATERI ARITMATIKA SOSIAL KELAS VII - Asmarita Asmarita; Rahmi Rahmi; Villia Anggraini (Universitas Muhammadiyah Metro, 2024)
The purpose of this study is to produce interactive learning media using macromedia flash on class VII social arithmetic material of SMP Negeri 3 Batang Anai Padang Pariaman Regency that is valid and practical. The type of research used is research and development (R&D) with the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). This research is only up to the implementation stage, because this research only develops valid and practical products. The instruments used in the study were validity questionnaires, and practicality questionnaires which were useful for seeing the practicality of interactive learning media by educators and students. Based on the results of the validity of learning media by validators, media experts and material experts, the final assessment percentage of the validity of interactive learning media was 85.7% with a very valid category. The final value of practicality with educators was 76.6% with the practical category and the final value of practicality with students was 87.25% with the very practical category. Based on the results of the study, it can be concluded that interactive learning media using macromedia flash on social arithmetic material is declared valid and practical.